Pembuatan Nata De Perepat sebagai Materi pada Pokok Bahasan Fermentasi di SMA Negeri 1 Tanjung Jabung Barat - Retni Sulistiyoning Budiarti; Harlis Harlis; Mia Aina; Raissa Martaniari (JPM: Jurnal Pengabdian Masyarakat, 2022)
One of the service activities carried out by the academic community of FKIP Jambi University is providing information about the making of nata de perepat which is being carried out at SMA N 1 Tanjung Jabung Barat. The condition of the area which is dominated by mangrove plants makes this area a commodity producing fasteners. The work methods that have been carried out include: demonstrations or performances interspersed with lecture and question and answer methods. The resource person shows the steps for making nata, then asks questions and answers about things that are not understood. As a continuation of this activity, there was a cooperation agreement to practice biology subject teachers directly to be applied during the learning process in fermentation. The results of the initial observations obtained through interviews with one of the teachers and several students at SMAN 1 Tanjung Jabung Barat that the mangrove area has never been used as a learning resource where students can take contextual knowledge in everyday life. One alternative solution that can be done is to utilize the perepat fruit that is in the environment by processing it into nata de perepat which has a high enough nutritional value for the surrounding community, in particular it can increase the knowledge and stale information of students at SMA Negeri 1 Tanjung Jabung Barat regarding fruit processing.